Instant Rice Analog Soybean Edamame and Seaweed: Antioxidant Activity and Color Intensity Studies - Micho Widyanto, Rahma; Ath-Thayyiba Utomo, Salsabil; Ayu Istifiani, Lola; Sarita Rahmawati, Irma; Tsalissavrina, Iva; Dian Nurhayati, Aprinia (MEDIA ILMU KESEHATAN, 2025)
Background: Rice is the most significant carbohydrate source of calories consumed throughout the world. Excessive consumption of rice is associated with the risk of Type 2 Diabetes Mellitus (T2DM). Analog instant rice made from edamame soybeans and seaweed can be used as an alternative for T2DM patients. Natural sources of antioxidants, such as those found in edamame soybeans and seaweed, can effectively reduce complications caused by diabetes.Objective: This research aimed to determine the value of antioxidant activity and colour intensity and also relationship between the two parameters.Methods: This research used a Completely Randomized Design, using 3 replications with control treatment: P1 (commercial instant white rice), and 3 treatments: P2;P3;P4 with percentage of edamame and seaweed flour= 40:60, 50:50, 60:40, repectively. Antioxidant activity and color intensity assay was conducted using the D.P.P.H. method and Hunter's Lab Colorimetric System.Results: The results showed that the highest antioxidant activity was shown in P4 with an IC50 value of 284.3±18.9 µg/mL. The highest value for the brightness, redness, and yellowness was obtained at P2, P4, and P3, respectively. Conclusion: The correlation test results showed no relationship between the colour intensity test parameters and the antioxidant activity in samples